Determination of neutron moderation parameters through neutron captured gamma ray emission – A novel method. (15th June 2022) - Hosamani, M.M.; Vinayak, A.; Hiremath, G.B.; Patil, Prashant N.; Badiger, N.M.
Abstract: The neutron moderation properties such as relative thermal lethargy, average logarithmic energy decrement and average number of collisions for elemental and composite materials were determined experimentally by using (n, γ) reaction. The Am-Be source used in the experiment emits neutrons of energies from thermal to fast with an average energy of 4.2 MeV along with the emission of 4.43 MeV gamma radiation due to de-excitation of 12 C* nucleus. The 2.2 MeV gamma radiation emitted from paraffin due to capture of thermal neutrons by hydrogen in paraffin and 4.43 MeV gamma radiations emitted due to de-excitation of 12 C* nucleus were detected with 2 in. × 2 in. NaI(Tl) gamma ray scintillation spectrometer coupled to multi-channel analyzer. Using the intensity ratio of 2.2 MeV and 4.43 MeV gamma radiations, the neutron moderation parameters have been determined for elemental targets such as C, Al, Fe, Cu, Zn, Pb and for composite materials such as Perspex, Cadmium Acetate dihydrate, Magnesium Acetate tetrahydrate, Cobalt Acetate tetrahydrate, Nickel Acetate tetrahydrate and Brass.